Bioconversion of wastewater-derived cresols to methyl muconic acids for use in performance-advantaged bioproducts. Issue 9 (13th April 2022) - Henson, William R.; Rorrer, Nicholas A.; Meyers, Alex W.; Hoyt, Caroline B.; Mayes, Heather B.; Anderson, Jared J.; Black, Brenna A.; Jayakody, Lahiru; Katahira, Rui; Michener, William E.; VanderWall, Todd A.; Salvachúa, Davinia; et al.
Abstract : We combine metabolic engineering and polymer chemistry to convert cresols, a main component of biomass-derived catalytic fast pyrolysis wastewater, to methyl muconic acids that have performance-advantaged properties in nylons and plasticizers. Abstract : Catalytic fast pyrolysis of biomass is a promising technology to generate biofuel blendstocks. This process generates a carbon-rich wastewater, which represents a loss of carbon that could be converted to co-products. Here, we explored the biological conversion of methyl phenols (cresols), a major component of biomass pyrolysis wastewater, into 2-methyl and 3-methyl muconic acids for use as polymer building blocks and plasticizers. We engineered Pseudomonas putida KT2440 to convert all three cresol isomers, o -, m -, and p -cresol, into their methyl muconic acid counterparts via the heterologous aromatic hydroxylase DmpKLMNOP from Pseudomonas putida CF600. We optimized conversion of cresols by expressing a heterologous (methyl)catechol dioxygenase ClcA from Rhodococcus opacus 1CP, followed by proof-of-concept fed-batch bioreactor cultivations. Methyl muconic acids and the hydrogenated methyl adipic acids were incorporated into nylons and plasticizers to evaluate potential performance advantages relative to existing materials. Methyl muconic acids in nylon-6, 6 analogs substantially reduced melting and glass transition temperatures and enable post-polymerization modifications, and incorporating methyl adipic acid into nylon-6, 6 analogs leads to a slightly reduced glass transition temperature and a 12% reduction in water permeability relative to nylon-6, 6. When methyl diacids were incorporated into plasticizers for poly(vinyl chloride), they exhibit lower glass transition temperatures at the same mass loadings as phthalic acid and adipic acid-based plasticizers. The methyl diacids were also predicted to exhibit reduced health and environmental risks compared to phthalic acid. Overall, this study encompasses the selection of a target product from an exemplary waste stream to the demonstration of multiple industrially relevant performance advantages relative to petroleum-derived analogs and highlights the potential for biological waste stream valorization.